A detailed study of tidal turbine power production and dynamic loading under grid generated turbulence and turbine wake operation. (May 2021) - Allmark, Matthew; Ellis, Robert; Ebdon, Tim; Lloyd, Catherine; Ordonez-Sanchez, Stephanie; Martinez, Rodrigo; Mason-Jones, Allan; Johnstone, Cameron; O'Doherty, Tim
Abstract: The paper presents an experimental campaign developed to contribute to the current research considering the operation of Horizontal Axis Tidal Turbines within stochastic flow conditions, namely turbulent and wake induced flows. The campaign was conducted at approximately a 1 / 20 t h -scale within a recirculating flume. Experiments were conducted over five differing setups, yielding a baseline low Turbulence Intensity case, two high turbulence cases and two upstream device generated wake cases. The experiments were conducted at a range of differing rotor velocities established, in a novel way, by utilising both fixed speed and fixed braking torque control. The paper presents analysis of flow measurements to statistically quantify the stochastic flow conditions impinging on the model-scale tidal turbine. The power, thrust, torque and blade root bending moment of single blade were recorded and analysed against the flow conditions generated under the five cases. The analysis showed that it may well be possible to exploit the accelerated region around an upstream turbine to capture marginally higher power (6 % increase) from downstream turbines. Lastly, it was found that the control scheme adopted has a significant impact on power and load fluctuations observed at differing rotor velocities. Highlights: Presents novel research into the combined effects of turbulence and devices. . Two differing control schemes are used fixed torque and speed control. The paper shows further evidence of the array 'packing' effect. The paper presents the effects of differing levels of TI on device loading.